2006
DOI: 10.1093/sleep/29.10.1353
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Actigraphy and Polysomnography in Older Adults Treated for Chronic Primary Insomnia

Abstract: The present findings suggest that the clinical utility of actigraphy is still suboptimal in older adults treated for chronic primary insomnia and should, hence, be used in this clinical setting with the concurrent use of supplementary assessment methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(126 citation statements)
references
References 22 publications
4
119
1
2
Order By: Relevance
“…Long-term monitoring of sleep requires more practical methods. Use of actigraphy, while a viable alternative, [7][8][9] is limited by the need for costly, specialized equipment and may be considered cumbersome by some patients. A reliable, affordable and user-friendly smartphone-based app that can monitor sleep-wake cycles would be an invaluable addition to the arsenal at the disposal of practitioners of sleep medicine.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term monitoring of sleep requires more practical methods. Use of actigraphy, while a viable alternative, [7][8][9] is limited by the need for costly, specialized equipment and may be considered cumbersome by some patients. A reliable, affordable and user-friendly smartphone-based app that can monitor sleep-wake cycles would be an invaluable addition to the arsenal at the disposal of practitioners of sleep medicine.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…7,9 Several studies have shown that, as with most devices that rely on movement-based algorithms, actigraphy has a high sensitivity but poor specificity in detecting sleep, and as a result its accuracy suffers as sleep efficiency decreases. 8 This raises the question as to whether using the app might represent an unobtrusive, cost-effective alternative to actigraphy with no loss of reliability. However, any further discussion needs to be tempered by the fact that such calculations for actigraphy are based on more traditional 30-or 60-sec epochs.…”
Section: (20%)mentioning
confidence: 99%
“…For insomniacs actigraphy can provide information about circadian rhythms and sleep patterns (Morgenthaler et al, 2007). Compared with polysomnography, however, actigraphy in insomniacs has had variable results: it has been found to both over and underestimate total sleep time (Vallieres & Morin, 2003;Sivertsen et al, 2006;Sadeh & Acebo, 2002). Another study found that actigraphy was well validated by polysomnography with respect to number of awakenings, wake time after sleep onset, total sleep time, and sleep efficiency (Lichstein et al, 2006).…”
Section: Collateral Sources Interviewmentioning
confidence: 99%
“…Actigraphy -Actisleep Device Polysomnography(PSG) is considered the "gold standard," for sleep study, however, they are expensive, often requiring participants to sleep in a laboratory, limiting their usability [14]. Wrist actigraphy is an acceptable alternative objective method to assess sleep duration [15].…”
Section: Study Evaluationmentioning
confidence: 99%